Physiological effects of high and low medetomidine doses in combination with zolazepam/tiletamine for the immobilisation and anaesthesia of spotted hyenas (Crocuta crocuta) - Tordiffe, Adrian Stephen Wolferstan (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.